2018
DOI: 10.17957/ijab/15.0560
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial Activity of Kaempferia galanga Essential Oil

Abstract: Kaempferia galanga L. is a traditional herbal medicine with high essential oil content. Gas chromatography-mass spectrometry (GC-MS) detected 25 different compounds in K. galanga essential oil, representing 95.98% of the total oil. The antibacterial activity of the essential oil was measured by the microtiter broth dilution method, and minimum inhibitory concentrations (MICs) against the three pathogenic bacterial strains Escherichia coli, Salmonella typhimurium and Staphylococcus aureus were 5, 1, and 2 mg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Ethyl p -methoxycinnamate ( 105 ) also isolated from K. galanga rhizomes have been shown based on a resazurin micro-titer assay to inhibit Mycobacterium tuberculosis H37Ra, H37Rv, multidrug-resistant, and drug-susceptible isolates with MIC 0.242–0.485 mM [27]. Its essential oil also displays strong antibacterial activity against Staphylococcus aureus and Salmonella typhimurium , and weak activity against Escherichia coli [28]. Moreover, essential oils extracted from three varieties of K. galanga exhibited potent larvicidal activity [29].…”
Section: Biological Activitymentioning
confidence: 99%
“…Ethyl p -methoxycinnamate ( 105 ) also isolated from K. galanga rhizomes have been shown based on a resazurin micro-titer assay to inhibit Mycobacterium tuberculosis H37Ra, H37Rv, multidrug-resistant, and drug-susceptible isolates with MIC 0.242–0.485 mM [27]. Its essential oil also displays strong antibacterial activity against Staphylococcus aureus and Salmonella typhimurium , and weak activity against Escherichia coli [28]. Moreover, essential oils extracted from three varieties of K. galanga exhibited potent larvicidal activity [29].…”
Section: Biological Activitymentioning
confidence: 99%
“…Volatile oils are generally composed of esters, hydrocarbons, terpenes and aromatic compounds. The 19 major compounds of essential oils are esters and terpenoids such as ethyl cinnamate, p-methoxycinnamate, pentadecane, δ-selinene, borneol, eucalyptol ( Fan et al, 2005 ; Zhou et al, 2006 ; Zhang, 2007 ; Cui et al, 2008 ; Wang et al, 2009 ; Sutthanont et al, 2010 ; Liu et al, 2014 ; Luo et al, 2014 ; Raina and Abraham, 2016 ; Yang et al, 2018 ) ( Table 4 ; Figure 2 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…(KGPs) were extracted and purified for the first time, and further investigated by different spectroscopic techniques such as HPGPC, FTIR, IC. Results showed that fucose (80), arabinose (81), xylose (82), rhamnose (83), mannose (84), galactose (85), glucose (86), glucuronic acid (87), and galacturonic acid (88) were the main components of KGPs, and their the molar ratio is 0.37: 3.12: 1.23: 3.09: 1.00: 6.39: 1.36: 0.91: 1.27, which significantly indicated that KGPs were heterogeneous acidic polysaccharides ( Yang et al, 2018 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…According to [23], Kencur essential oil showed strong inhibitory activity against Salmonella typhimurium, Staphylococcus aureus and Escherichia coli. Antimicrobial activity can occur due to membrane damage, cell wall damage and damage to electron transport [24].…”
Section: A Activity Of Inhibition Zone Of Hard Candy With Kencur Essential Oilmentioning
confidence: 99%
“…Antimicrobial activity can occur due to membrane damage, cell wall damage and damage to electron transport [24]. The mechanism of changes that occur due to the administration of Kencur essential oil has been reported in study by [23], where the use of essential oils causes structural changes in bacterial cells as well as nucleic acids and causes proteins to undergo lysis, eventually leading to cell damage. Giving Kencur essential oil causes bacterial cells to stick together, cell membranes to undergo lysis and changes in bacterial morphology, including severe damage, defects, holes and wrinkles.…”
Section: A Activity Of Inhibition Zone Of Hard Candy With Kencur Essential Oilmentioning
confidence: 99%